Classification of factors contributing to sustainable issues on selected traditional Malay houses and bio-climatic buildings / Roslan Talib and Mohd Zailan Sulieman - Talib, Roslan; Sulieman, Mohd Zailan (2012)
The concept of sustainable building incorporates and integrates a variety of strategies during the design, construction and operation of building projects. The use of green building materials and products represents one important strategy in the design of a building. Green building materials offer specific benefits to the building owner and building occupants which are reduced maintenance or replacement costs over the life of the building, energy conservation, improved occupant health and productivity, lower costs associated with changing space configurations and greater design flexibility. Thus, we must look back into the traditional way of house designed where the green impact play an important role in producing much sensitive structure with intune with the environment. The designers especially the interior designer with fair knowledge on environmental friendly designs or in today term as design with sustainable or green design factors must play lead role. Therefore, with the above goals, this paper become an initial platform trying to measure on the selected Malay houses and current bio-climatic designed structures sensitivity in applying interior and exterior design sustainable issues into the buildings. This study however will discuss on the comparative green design factors that addresses sustainability through an environmentally based research focus. Therefore, this study examines the environmental conditions of a continuing practice of the sustainable design from the early culture until now.